Religious Information Literacy in Digital Learning from an Islamic Education Perspective: An Analysis of Ellis's Information Seeking Behavior Model - Siti Isnaini (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze religious information literacy in digital learning based on the perspective of Ellis's Information Seeking Behavior Model and examine its relevance to the principles of Islamic education. This study uses a qualitative approach with library research. Data was obtained from primary sources in the form of the works of David Ellis and its development by Cox and Hall regarding Information Seeking Behavior. Meanwhile, secondary data was obtained from books, articles, proceedings, and previous research results that discuss digital information literacy. Data collection was carried out through documentation studies, while data analysis used content analysis techniques that include data reduction, categorization, interpretation, and synthesis of various relevant sources. The results of the study indicate that Ellis's Information Seeking Behavior Model, which consists of eight stages (starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending) can be used as a conceptual framework for strengthening religious information literacy in digital learning. Furthermore, these stages are also relevant to Islamic educational principles, such as the importance of critical thinking, learning motivation, perseverance in learning, teacher guidance, and continuous learning. Thus, integrating the Ellis Model with Islamic educational principles can provide an alternative framework for religious information literacy in digital learning that is more critical, selective, and responsible.